Sylvaemus uralensis (Rodentiformes, Muridae) в Восточных Карпатах - Киселюк, А.И. (Вестник зоологии, 1993)
First record of the species for the high montane Carpathians, data on its biology under montane environment, comparative morphological characteristics of mountain and lowland specimens.